Capital Control Measures : A New Dataset - Fernandez, Andres; Klein, Michael; Rebucci, Alessandro; Schindler, Martin (Washington, D.C. : International Monetary Fund, 2015)
This paper presents a new dataset of capital control restrictions on both inflows and outflows of 10 categories of assets for 100 countries over the period 1995 to 2013. Building on the data in Schindler (2009) and other datasets based on the analysis of the IMF's Annual Report on Exchange Arrangements and Exchange Restrictions (AREAER), this dataset includes additional asset categories, more countries, and a longer time period. The paper discusses in detail the construction of the dataset and characterizes the data with respect to the prevalence and correlation of controls across asset categories and between controls on inflows and controls on outflows, the aggregation of the separate categories into broader indicators, and the comparison of this dataset with other indicators of capital controls.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet